2017
DOI: 10.1002/stem.2541
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Microvesicles Modulate Lipopolysaccharides-Induced Inflammatory Responses to Microglia Cells

Abstract: Microglia cells are the central nervous system immune cells and have been pointed out as the main mediators of the inflammation leading to neurodegenerative disorders. Mesenchymal stromal cells (MSCs) are a heterogeneous population of cells with very high self-renewal properties and uncomplicated in vitro culture. Research has shown that MSCs have the capacity to induce tissue regeneration and reduce inflammation. Studies demonstrated that MSCs have complex paracrine machineries involving shedding of cell-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 55 publications
4
85
0
Order By: Relevance
“…A variety of trophic factors and cytokines with immunomodulatory, anti‐inflammatory, and anti‐apoptotic activity has been identified as a result (Drago et al, ; Konala et al, ). MSC‐derived microvesicles show strong and acute immune modulatory activity, reducing MAPK and STAT activity within hours (Jaimes, Naaldijk, Wenk, Leovsky, & Emmrich, ). In other studies, TNFα‐stimulated gene‐6 (TSG6), identified as an active component of the MSC secretome, shows an anti‐inflammatory effect in LPS‐stimulated microglia and reduces phosphorylation of STAT1 (Liu et al, ; Mittal et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of trophic factors and cytokines with immunomodulatory, anti‐inflammatory, and anti‐apoptotic activity has been identified as a result (Drago et al, ; Konala et al, ). MSC‐derived microvesicles show strong and acute immune modulatory activity, reducing MAPK and STAT activity within hours (Jaimes, Naaldijk, Wenk, Leovsky, & Emmrich, ). In other studies, TNFα‐stimulated gene‐6 (TSG6), identified as an active component of the MSC secretome, shows an anti‐inflammatory effect in LPS‐stimulated microglia and reduces phosphorylation of STAT1 (Liu et al, ; Mittal et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that the MSC‐derived microvesicles significantly reduced levels of inflammatory cytokines of the hyperoxia‐induced injured lungs and also contains several beneficial anti‐inflammatory factors for wound healing (Ahn et al, ; Sung et al, ). It has been also known that MSC‐derived microvesicles have potency to modulate microglial activation by suppressing MAPK (Jaimes et al, ). These findings suggest that microvesicles included in MSC‐CM in this study might have a seminal role for strong and acute immune modulatory effects on microglia showing reduced MAPK and STAT activity within hours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, BM-MSC-derived microvesicles downregulated the level of IL-1β, IL-6, TNF-α, iNOS, and PTGS2, produced by microglia cells, when cocultured in LPS inflammatory environment. Moreover, the phosphorylation of ERK, JNK, and p38 molecules in microglia cells was also suppressed by BM-MSC-derived microvesicles [111]. In an uninflamed environment, DPSCs were shown to induce the production of TNF-α by macrophages via PKR-rich microvesicles [112].…”
Section: Oral Msc-derived Extracellular Vesicles (Evs) In Conditionedmentioning
confidence: 98%
“…Target cells of MSC-derived exosomes include fibroblasts, MSCs, epithelial cells, and immune cells (24). It is partially through this exosome-mediated mechanism that MSCs exert their anti-inflammatory effect in vitro (24,25). The role of exosomes in the treatment of lung disease is an area of active pre-clinical study.…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%